Juan Meserón: the life of a musician framed in the crisis of the colonial system (Revista Electrónica REDINE, 2018)
The History of Venezuela is plagued by episodes of a certain political polarization. The most notable of these was the period in which the decline of the colonial system was described. For that reason, this study has a purpose to contextualize the life of the composer Juan Meserón in order to have a closer approximation of his biography. For this intention the Phases of the crisis of the Venezuelan colonial system described by Germán Carrera Damas (1983) are used as a guide to locate the historical events and deepen the life of the musician in study. This has allowed us to see the qualities of a Venezuelan, who, although in a principle of apparent ideological difference, was a true builder of society; being, the present document, a contribution to the revision of the historical awareness of our identity.
Keywords: musicology; history of music; Juan Meserón